TED-Talk through Language Reactor in Enriching Students’ English Vocabulary for University Level - Nasrullah, Naufal Siddiqi; Aini, Nurul (Proceeding International Conference on Religion, Science and Education, 2024)
The problem of students’ boredom in learning English vocabulary has become a crucial challenge in English language teaching (ELT). Therefore, Website-based language learning (WBLL) was an important aspect of tackling the problem. Integrating TED-talk and Language Reactor Toolbox for vocabulary learning was the new concept developed by the researchers in this study. The present article aimed to discuss the TED Talk and Language Reactor to improve students’ vocabulary learning using dual subtitles. This paper used the conceptual research design that focused on conceptual models with conceptual descriptions. This article signified for academics to support the literature review as references for their research and development study. The findings showed that TED-Talk and LRT can be integrated as a new concept of vocabulary learning to increase students' interest as well as enriching students vocabulary. Moreover, the present article provided a gateway to the research and development study of TED-Talk and Language for vocabulary learning. Future research could develop the E-module to realize this concept.